A New Era for Rotational Atherectomy: An Australian Perspective. Issue 13 (May 2019) - Bamford, Paul; Parkinson, Michael David; Gunalingam, Brendan; David, Michael; Lau, George Tat-Ming
Background: Rotational atherectomy (RA) has been used in percutaneous coronary intervention (PCI) for 30 years. With advances in technology, this observational study looks at how rates of RA have changed over the past decade in Australia in relation to PCI and coronary artery bypass graft (CABG) rates. Methods: Retrospective analysis of RA, PCI, and CABG rates per Australian state from Australian Government Department of Human Services' data on Medicare items from 2007 to 2017 was carried out. Results: There were 149 RA procedures in 2007, increasing to 452 in 2017. Rotational atherectomy accounted for 0.67% of PCI procedures in 2007, increasing to 1.48% in 2018 (+0.81%, 95% confidence interval [CI] = [0.64%-0.91%]; P  < .001). Most of this increase has come from procedures in New South Wales (441% increase). Australian PCI rate increased from 22 301 to 30 480. Rate of CABG decreased from 5418 to 5206. Conclusions: From 2007 to 2017, rates of RA trebled in Australia. This is despite stable rates of PCI and a fall in rates of CABG. There are several clinical explanations for this trend.